Determination of cetirizine in human plasma using high performance liquid chromatography coupled with tandem mass spectrometric detection: application to a bioequivalence study - Ren, Xiao-Lei; Tian, Yuan; Zhang, Zun-Jian; Chen, Yun; Wu, Li-Li; Huang, Jun (Arzneimittelforschung, 2011)
A rapid, sensitive and selective HPLC–MS/MS method was developed and validated for the quantification of cetirizine dihy-drochloride (CAS 83881-51-0) in human plasma using mosapride citrate as internal standard (IS, CAS 112885-42-4). Following liquid–liquid extraction, the ana-lytes were separated using a mobile phase consisting of methanol and aqueous ammonium acetate solution (10 mM) (60 : 40, v/v) on a reverse phase C18 column and analyzed by a triple-quadrupole mass spectrometer in the selected reaction monitoring (SRM) mode using the respective [M+H]+ ions, m/z 398 → 201 for cetirizine and m/z 422 → 198 for mosapride. The analysis time for each run was 8.0 min. The assay exhibited a linear dynamic range of 0.5–500 ng/ml for cetirizine dihydrochloride in human plasma. The lower limit of quantification (LLOQ) was 0.5 ng/ml with a relative standard deviation of less than 15% (all the concentration data in this study related to the salt (cetirizine dihydrochloride)). Acceptable precision and accuracy were obtained for concentrations over the standard curve range. It is the first time that the validated HPLC–MS/MS method has been successfully applied to a bioequivalence study in 20 healthy male Chinese volunteers.
Keywords: Bioequivalence; Cetirizine dihydrochloride; HPLC-MS/MS; Human plasma